(untitled) (Research, Society and Development, 2022)
Family socioeconomic and environmental conditions are associated with health status and disease outcomes in infancy, acting at different levels of determination over these events, positively or negatively affecting individuals. Methods was adopted a hierarchical approach to investigate a vitamin D insufficiency and socioecomimc determinants in the basic, intermediate, and immediate levels. The logistic regression and odds ratio (OR) as an association measure were used to assess the relationship of interest. The prevalence of vitamin D insufficiency (10-29.9 ng/ml) was 54.1% of the adolescents, no vitamin D deficiency (<10 ng/ml) was identified. At the basic level, was observed a 52% protective effect (OR = 0.48; p< 0.003) of the low socioeconomic stratum for the occurrence of insufficient vitamin D levels; living in rural area increased by 2.35 times more chances of having insufficient vitamin D levels (OR = 2.35; p < 0.001). At the intermediate level, the sanitary conditions of the household situated at the lowest level of the distribution tercile, resulted in a 1.41% higher risk (OR = 2.41; p < 0.034) of those conditions being associated with vitamin D insufficiency. At the immediate level, the results showed that those with 14-years had 2.37 times more chances (OR = 2.37; p < 0.024) and to be black/brown skin (OR = 2.00; p < 0.047) were associated with vitamin D insufficiency. Conclusion socioeconomics factors and individual level were associated with vitamin D insufficiency in adolescents.